Cinética do consumo de oxigênio e tempo limite na vvo2max: comparação entre homens e mulheres - Azevedo, Paulo Henrique Silva Marques De; Oliveira, João Carlos De; Simões, Herbert Gustavo; Baldissera, Vilmar; Perez, Sérgio Eduardo De Andrade (Sociedade Brasileira de Medicina do Exercício e do Esporte, 2010)
The aim of this study was to investigate the influence of gender on Tthre and VO2 response during running exercise performed at vVO2max. Therefore, eighteen untrained individuals (9 male and 9 female) with normal weight and aged between 20 - 30 years (VO2max = 42.66 ± 4.50 vs 32.92 ± 6.03 mL.kg-1.min-1 and vVO2max = 13.2 ± 1.5 vs 10.3 ± 2.0 km.h-1, for male and female, respectively) were assessed. Subjects performed two exercise tests on treadmill. First one was an incremental test to determine VO2max, velocity at VO2max (vVO2max) and second test was performed at steady velocity - vVO2max - until exhaustion. The threshold time (Tthre) and VO2 kinetics response was determined. No significant differences were observed between men and women for time constant (τ) (35.76 ± 21.03 vs 36.5 ± 6.21s, respectively; P = 0.29); Tthre (308 ± 84.3 vs 282.11 ± 57.19s, respectively; P = 0.68), time to achieve VO2max (TAVO2max) (164.48 ± 96.73 vs 167.88 ± 28.59s, respectively; P = 0.29), time to achieve VO2max in Tthre percentage (%Tthre) (50.24 ± 16.93 vs 62.63 ± 16.60%, respectively; P = 0.19); time maintained at VO2max (TMVO2max) (144.08 ± 42.55 vs 114.23 ± 76.96s, respectively; P = 0.13). These results suggest that the VO2 kinetics response and Tthre is similar between untrained men and women at the vVO2max.

Foi investigada a influência do gênero no tempo limite (Tlim) e na cinética do VO2 durante corrida na velocidade associada ao VO2max (vVO2max) em nove homens e nove mulheres, todos adultos, jovens e sedentários, com idades entre 20 e 30 anos. Homens e mulheres realizaram dois testes em esteira rolante, sendo um teste incremental para determinar VO2max (42,66 ± 4,50 vs. 32,92 ± 6,03mL.kg-1.min-1) e vVO2max (13.2 ± 1.5 vs. 10,3 ± 2,0km.h-1), respectivamente. Um segundo teste com carga constante na vVO2max até a exaustão. O Tlim e a cinética do VO2 foram determinados. Não houve diferença significante entre homens e mulheres para constante de tempo (τ) (35,76 ± 21,03 vs. 36,5 ± 6,21s, respectivamente; P = 0,29); Tlim (308 ± 84,3 vs. 282,11 ± 57,19s, respectivamente; P = 0,68), tempo para atingir o VO2max (TAVO2max) (164,48 ± 96,73 vs. 167,88 ± 28,59s, respectivamente; P = 0,29), tempo para atingir o VO2max em percentual do Tlim (%Tlim) (50,24 ± 16,93 vs. 62,63 ± 16,60%, respectivamente; P = 0,19), tempo mantido no VO2max (TMVO2max) (144,08 ± 42,55 vs. 114,23 ± 76,96s, respectivamente; P = 0,13). Estes resultados sugerem que a cinética do VO2 e o Tlim são similares entre homens e mulheres sedentários na vVO2max.
Oxygen uptake kinetics and threshold time at the vVO2max: tomparison between men and women
Keywords: gender; exhaustion time at VO2max; VO2 kinetics; gênero; tempo para exaustão na vVO2max; cinética do VO2